Seakeeping Of A 60 Gt Cast Nets Fishing Vessel At Muara Angke Fishing Port - Arif Fadillah; Nadia Nadia (Zona Laut : Jurnal Inovasi Sains Dan Teknologi Kelautan, 2024)
Based on the provisions made by the International Maritime Organization (IMO), turning ability and zig-zag maneuvers are the main criteria for safety standards for every ship that will sail. This decree was made as an effort to improve sailing skills, especially for ship crew. Calculation of the turning ability of a ship is greatly influenced by the design of the ship's hull and the design of the rudder that will be used on the ship. So the analysis of turning circles and zig-zag maneuvers is the main point that will be carried out in this research. The research was carried out on cast net vessels anchored at the Muara Angke fishing port with the vessel size taken being 60 GT. The standard provisions used in the analysis of turning ability and zig-zag maneuver are based on IMO MSC 137 (76) with the main size of the vessel used as the main research material is LOA=25.7 m, LPP =22.2 m, B=7 m, H=2.3 m, T=1.7 m. With the results obtained by the movement of the fishing vessel which meets standardization based on IMO MSC 137 (76) 2002, the turning circle maneuver has a Tactical Diameter of 46.07 m, with an Advanced value of 56.23 m, with a heading transfer value of 24.48 m, the zig-zag maneuver meets the IMO standard criteria stated for angels 10°/10° and 20°/20° do not exceed 30 seconds